Minimum time overtaking problem of vehicle handling inverse dynamics based on interval mathematics. (May 2019) - Zhao, Youqun; Zhang, Wenxin; Zhang, Xinglong; Lin, Fen
To analyze the influence of uncertain factors on minimum time overtaking, interval mathematics is used to describe the uncertainties, and the overtaking safety distance is calculated using interval analysis method. In addition, vehicle handling inverse dynamics is proposed in this paper. In this method, the driver-handling input can be obtained without the modeling of driver. The optimal control problem is first converted into a nonlinear programming problem based on Gauss pseudospectral method. Then sequential quadratic programming is applied to get the solution. The simulation results show that the overtaking behavior will be significantly different, if the drivers' age groups or vehicles' braking system parameters are different. Besides, the influence of different drivers' estimate time is critical. The subjective judgments of the drivers are considered in this paper to realize the user-friendly design. This method may provide a reference for the research of unmanned vehicles and driving assistance system.